Negative-hydrogen-ion production from a nanoporous 12CaO ∙ 7Al2O3 electride surface. (8th May 2018) - Sasao, Mamiko; Moussaoui, Roba; Kogut, Dmitry; Ellis, James; Cartry, Gilles; Wada, Motoi; Tsumori, Katsuyoshi; Hosono, Hideo
Abstract: A high production rate of negative hydrogen ions (H − ) was observed from a nanoporous 12CaO ∙ 7Al2 O3 (C12A7) electride surface immersed in hydrogen/deuterium low-pressure plasmas. The target was negatively biased at 20–130 V, and the target surface was bombarded by H3 + ions from the plasma. The production rate was compared with that from a clean molybdenum surface. Using the pseudo-exponential work-function dependence of the H − production rate, the total H − yield from the C12A7 electride surface bombarded at 80 V was evaluated to be 25% of that from a cesiated molybdenum surface with the lowest work-function. The measured H − energy spectrum indicates that the major production mechanism is desorption by sputtering. This material has potential to be used as a production surface of cesium-free negative ion sources for accelerators, heating beams in nuclear fusion, and surface modification for industrial applications.